Energy Crisis and Productive Inefficiency: Micro-Evidence from Textile Sector of Faisalabad (The Pakistan Development Review, 2013)
Energy, being an essential component of every production process, plays a pivotal role in the growth process of a country. The production process has undergone a massive transition from labour intensive to energy intensive techniques [Stern and Cleveland (2004)]. Now, it is widely recognised that industrialisation is an energy-intensive process; hence, uninterrupted supply of energy is necessary to keep the production process in run. In addition, high percapita energy consumption is considered as an indicator of the level of economic development. This positive correlation between energy consumption and output growth (and development) led many countries, particularly developing ones, to design policies for subsidised energy provision with focus on supply-side in late eighties. At the same time, some European countries (i.e. Germany, Denmark, Belgium, Sweden) formulated energy policy focusing on demand-side (energy conservation), and achieved smaller growth rates in energy consumption without any reduction in economic growth [Pintz (1986)].